Association between pill burden and interdialytic weight gain in patients with hemodialysis: A multi‐center cross‐sectional study. Issue 4 (20th November 2020) - Murasawa, Masaru; Uehara, Atsuko; Suzuki, Tomo; Shimizu, Sayaka; Kojima, Shigeki; Uchida, Daisuke; Okamoto, Takeshi; Naganuma, Toru; Sasaki, Sho; Imai, Naohiko; Chikaraishi, Akihiro; Matsukawa, Shigeaki; et al.
Abstract: High daily pill burden affects quality of life and mortality. High interdialytic weight gain (IDWG) is associated with increased mortality. We examined the association between pill burden and IDWG in hemodialysis patients. This cross‐sectional study was conducted in six dialysis centers in Japan in June 2017. The exposure was the number of daily tablets, and outcome was defined as 1 day of relative IDWG divided by post‐dialysis weight from the previous session. Among 188 outpatients (mean age, 68.7 [SD, 10.3] years; men, 67.0%; median dialysis vintage, 76.0 [interquartile range, 36.5, 131.5] months), the mean number of daily tablets was 19.7 ± 9.9, and mean relative weight gain was 3.5 ± 1.2%. Multiple linear regression analysis showed a regression coefficient of 0.021 (95% confidence interval: 0.004‐0.039), indicating that one additional tablet prescription increased the IDWG by 0.021%. In hemodialysis patients, the daily pill burden was a significant, independent risk for increased relative IDWG.